Evaluation of HE4 and IGFBPs as Novel Biomarkers of Systemic Lupus Erythematosus with Lupus Nephritis - NoorAlhuda Kh. Ibrahim1 , Kadhim K. Ghudhaib2 , Ali Abdulmajid Dyab Allawi 3, Faten Abdulghani Hammo (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: many organs of the body such as kidneys, skin, joints, nervous system, blood cells, bloodvessels and serous membranes can be affected by systemic lupus erythematosus (SLE). A wide range ofthis disease effects may be attributed to its behavior as an autoimmune disease; this means, numerouscomplications of SLE with many organs can be results. In this study, levels of serum human epdidymissecretory protein4 (HE4) and insulin like growth factor binding protein-2 (IGFBP-2) for Iraqi patients inSLE with and without lupus nephritis (LN) were investigated to knowledge their ability to be useful markersfor identification of kidney diseases, like lupus nephritis and chronic kidney disease in patients who sufferingfrom SLE.Methods: one hundred twenty subjects from both sexes were enrolled in this study. They have been classifiedinto two patients groups together with the control group. Forty patients of SLE with LN (8male-32female)with age range (19-44) years, represent the first patients group, the second patients group includes fortypatients suffer from SLE without LN at (16-45) years age range and the control group which consists of 40healthy subjects with age range (19-62) years. HE4 and IGFBP were estimated by ELISA method.Results: results show high level of HE4 and IGFBP in both patient groups with SLE in comparison withcontrol group. At the same time, results confirmed a high positive correlation between HE4 and IGFBP (r =0.85, p<0.01), ROC analysis data revealed that HE4 is the best parameters for predicting development lupusnephritis as a main complication of SLE disease.Conclusion: both patient groups revealed a significantly increase in levels of HE4 and IGFBP comparedwith control group. High positive correlation coefficient between HE4 and IGFBP is obtained. Data of ROCanalysis confirmed that HE4 represents a better biomarker for diagnosis of LN in patients with SLE disease.